Neurologic outcome in patients with cardiac arrest complicating ST elevation myocardial infarction treated by mild therapeutic hypothermia: The experience of a tertiary institution - Emre Aruğaslan (Türk Kardiyoloji Derneği Arşivi, 2016)
Objective: Therapeutic hypothermia improves neurologic prognosis after cardiac arrest. The aim of this study was to report clinical experience with intravascular method of cooling in patients with cardiac arrest resulting from ST-segment elevation myocardial infarction (STEMI). Methods: Thirteen patients (11 male, 2 famele; mean age was 39.6+-9.4 years) who had undergone mild therapeutic hypothermia (MTH) by intravascular cooling after cardiac arrest due to STEMI were included. Clinical, demographic, and procedural data were analyzed. Neurologic outcome was assessed by Cerebral Performance Category (CPC) score. Results: Anterior STEMI was observed in 9 patients. One patient died of cardiogenic shock complicating STEMI. Mean cardiopulmonary resuscitation (CPR) duration and door-toinvasive cooling were 32.9+-20.1 and 286.1+-182.3 minutes, respectively. Precooling Glasgow Coma Scale score was 3 in 9 subjects. Twelve patients were discharged, 11 with CPC scores of 1 at 1-year follow-up. No major complication related to procedure was observed. Conclusion: In comatose survivors of STEMI, therapeutic hypothermia by intravascular method is a feasible and safe treatment modality.